Implementation of Ruang Belajar Aqil (RBA) Program in Improving Social Empowerment in Karangsari Village, Bantur District, Malang Regency - Ina Urifah; Renny Oktafia (IJCS: International Journal of Community Service, 2023)
Karangsari Village is one of the villages in Bantur District, Malang Regency. There is a lot of potential including natural resources and human resources that can be developed. However, the level of education and economy of the people in Karangsari Village is still relatively low. On the other hand, students' enthusiasm for learning is very high, but the lack of support and limited facilities make it difficult for students to develop. Lack of understanding and knowledge makes it difficult for people to create business opportunities. This shows that social empowerment in Karangsari Village has not been achieved. Therefore, to assist in overcoming this, it is necessary to implement social empowerment programs, one of which is Ruang Belajar Aqil (RBA) program. The method used in this service is ABDC (Asset Based Community Development). Data were collected through direct observation and documentation. The results obtained show that the implementation of Ruang Belajar Aqil (RBA) program provides positive changes in increasing social empowerment, especially in increasing the knowledge and creativity of the community in Karangsari Village.